PHASE TRANSFORMATION OF ARMENIAN ZEOLITES DURING HYDROTHERMAL MODIFICATION (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
On the basis of data of the chemical analysis and X-ray and electron-microscopy studies it was shown that the clinoptilolite modifies to other minerals of zeolite and alumosilicat group during hydrothermal treatment. The phase transformation processes are observed traced in conditions of the treatment (temperature, time, pressure, concentration and type of alkali). The parameters of the clinoptilolite stability in various conditions of thermal treatment are defined.
Keywords: Armenian zeolites; clinoptilolite; hydrothermal treatment; minerals of zeolite and alumosilicat group